2005
DOI: 10.1084/jem.20050158
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 receptor signaling is necessary for stage transition in adult B cell development through up-regulation of EBF

Abstract: Cytokine receptor signals have been suggested to stimulate cell differentiation during hemato/lymphopoiesis. Such action, however, has not been clearly demonstrated. Here, we show that adult B cell development in IL-7 −/− and IL-7Rα2/− mice is arrested at the pre–pro-B cell stage due to insufficient expression of the B cell–specific transcription factor EBF and its target genes, which form a transcription factor network in determining B lineage specification. EBF expression is restored in IL-7 −/− pre–pro-B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
221
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(245 citation statements)
references
References 32 publications
(60 reference statements)
22
221
2
Order By: Relevance
“…Recent data have indicated that the main action of IL7 signaling at the CLP stage involves the activation of STAT5 but not AKT-mediated signaling (25,26). In contrast, FLT3 signaling most likely activates the PI(3)K pathway until the FLT3 receptor is suppressed at later developmental stages by PAX5 (26). These latter observations raise the question as to how FOXO1 protein abundance is maintained in the presence of FLT3-mediated signaling.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Recent data have indicated that the main action of IL7 signaling at the CLP stage involves the activation of STAT5 but not AKT-mediated signaling (25,26). In contrast, FLT3 signaling most likely activates the PI(3)K pathway until the FLT3 receptor is suppressed at later developmental stages by PAX5 (26). These latter observations raise the question as to how FOXO1 protein abundance is maintained in the presence of FLT3-mediated signaling.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, we are now faced with the question as to whether IL7-and FLT3-mediated signaling modulates FOXO1 nuclear location and abundance. Recent data have indicated that the main action of IL7 signaling at the CLP stage involves the activation of STAT5 but not AKT-mediated signaling (25,26). In contrast, FLT3 signaling most likely activates the PI(3)K pathway until the FLT3 receptor is suppressed at later developmental stages by PAX5 (26).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the size and cellularity of the spleen were relatively normal. Then we analyzed the subsets of B-cell population as previously described [40], which is characterized by B220 Fig. 2A), and B220 + CD43 − IgM + IgD + (mature B cell, Fraction F in Fig.…”
Section: (C D) (C) Frequencies and (D) Absolute Numbers Of Pro-b (B220mentioning
confidence: 99%
“…For example, GM-colony-stimulating factor (GM-CSF) was shown to direct macrophage vs. neutrophil outcome in myeloid progenitors by regulating the CCAAT enhancer-binding protein-␣ (C͞EBP␣) and PU.1 expression levels (7). IL-7 was also demonstrated to up-regulate early B cell factor (EBF) expression level in preproB cell and promote transition to proB cell stage during B cell development (8). Nonetheless, it is not clear whether cytokines are involved in determining lymphoid vs. myeloid lineage decision in more primitive progenitors.…”
mentioning
confidence: 99%